2013
DOI: 10.1089/aid.2012.0378
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Combination Antiretroviral Therapy on Chinese Rhesus Macaques of Simian Immunodeficiency Virus Infection

Abstract: Definitive treatment of HIV infection remains a critical but elusive goal, with persistence of residual virus even in the face of prolonged administration of suppressive combination antiretroviral treatment (cART) providing a source for recrudescent infection if treatment is stopped. Characterization of the residual virus and devising strategies to target it for eradication are key goals in HIV treatment research. Indian rhesus macaques (In-RM) infected with SIVmac have been widely used in such research. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Rhesus macaques have emerged as a major model for studies of HIV (or SIV and SHIV) pathogenesis, evaluation of novel therapeutics or antivirals, as well as for vaccine development (Hansen et al, 2013; Ling et al, 2013; Zhou et al, 2013; Roederer et al, 2014). In addition, this model is widely used to investigate many other human pathogens as well as the efficacy of new vaccine candidates (reviewed by (Gujer et al, 2011)).…”
Section: Introductionmentioning
confidence: 99%
“…Rhesus macaques have emerged as a major model for studies of HIV (or SIV and SHIV) pathogenesis, evaluation of novel therapeutics or antivirals, as well as for vaccine development (Hansen et al, 2013; Ling et al, 2013; Zhou et al, 2013; Roederer et al, 2014). In addition, this model is widely used to investigate many other human pathogens as well as the efficacy of new vaccine candidates (reviewed by (Gujer et al, 2011)).…”
Section: Introductionmentioning
confidence: 99%
“…to study infectious diseases including simian immunodeficiency virus/ human immunodeficiency virus, avian influenza, malaria, plague, and severe acute respiratory syndrome, as well as studies of xenotransplantation, stem cell therapies, reproduction, and neurobiology (Shen et al 2007;Chen et al 2009Chen et al , 2011Chen et al , 2012Choi et al 2011;Liu et al 2011;Tian et al 2011;Wei et al 2011;Hutnick et al 2012;Li et al 2012b;Ling et al 2013;Mumbauer et al 2013). Yet comparatively little is known about the immunogenetics of these animals.…”
mentioning
confidence: 99%
“…MothĂ© et al [ 11 ] reported Ch-RM MHC immunogenetics are more similar to HLA than those of Indian macaques, and therefore that Ch-RMs might be a better model for HIV. The SIV-infected Ch-RM has been successfully used as a model for studying responses to combination antiretroviral therapy (ART) and evaluating candidate eradication strategies to cure HIV infection [ 12 ]. Our study was performed to develop a chronically SHIV89.6-infected Ch-RM model for detailed investigation of Chinese medicine therapeutic effects.…”
Section: Discussionmentioning
confidence: 99%